Purification of natural water from organic pollution by a modified microfiltration tubular ceramic mem brane from clay minerals - Dulneva, T.Yu.; Deremeshko, L.A.; Baranov, A.I.; Kucheruk, D.D.; Goncharuk, V.V. (Reports of the National Academy of Sciences of Ukraine, 2020)
Baromembrane methods implemented on ceramic membranes are promising for the water purification from natural organic pollutants. Studies on the purification of the Dnieper water were carried out on an experimental baromembrane unit, which operated in the flow-recirculation mode. It used a microfiltration ceramic tubular membrane made of clay minerals, developed in A.V. Dumansky Institute of Colloidal Chemistry and Water Chemistry of the NAS of Ukraine. The regularities of the process of purification of the Dnieper water from the organic compounds contained in it by this membrane modified by various substances such as hydroxyl compounds Fe(ІІІ) and aluminum, corn starch, and montmorillonite are studied. A modification of the ceramic membrane occurred by forming a dynamic membrane of the above substances on its surface. The process of its formation continued until the membrane reached almost constant values of its specific productivity, while the active layer of the dynamic membrane was in dynamic equilibrium. The dynamic membrane was formed by the steric mechanism based on the difference in pore sizes of the dynamic membrane and the particles of the membrane-forming substance with organic substances adsorbed on it. It is shown that, for the purification of the Dnieper water from organic substances to their maximum permissible concentration in water for the cent ralized water supply, it is advisable to use a ceramic membrane of clay minerals, which is dynamically modified with hydroxyl compounds of iron (III) at a concentration of Fe ions (III) in the membrane-forming and membrane-supporting additives, respectively, 90.0-100.0 and 20.0-22.0 mg/dm3, pH0 7.3; P 1.0 MPa. Ceramic membranes modified with the other indicated substances had, under optimal conditions, the worse separation properties.